Dans l’atelier du traducteur : Giorgio Caproni à l’épreuve de la poésie française - Bricco, Elisa (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
French poetry translation was a very enriching activity for the Italian poet Giorgio Caproni. In fact, rewriting the texts of other authors contributed to fulfil his poetic creation. The funds we have consulted contain some quite rich genetic dossiers useful to understand the translator’s methods and perspectives of work. In this paper, we analyze the preliminary texts of the translation of a poem by André Frénaud, "Passage of the Visitation", in order to retrace the steps of translation work and to point out the contribution of this work to personal translator’s poetic writing.